Harness agrifood value chains to help farmers be climate smart: Incentives and structures exist to improve farming practices - Swinnen, Johan; Ronchi, Loraine; Reardon, Thomas (American Association for the Advancement of Science, 2024)
Incentives and structures exist to improve farming practices